The Influence of Quantum Teaching and Learning (QTL) Model on Interests and Learning Outcomes of Chemistry - Uswatun Hasanah; Agus Kamaludin (Pendidikan Kimia Unimus, 2021)
This research aims to examine the effect of using the Quantum Teaching and Learning (QTL) model on students learning interests and outcomes on compound nomenclature material. The research was conducted in State Senior High School 8 Yogyakarta in the 10th grade of mathematics and natural science in the academic year of 2018/2019. This type of research was Quasi-Experimental Research Design with Nonequivalent Control Group Pretest and Posttest Design. The sampling technique was purposive sampling. The data collection instruments included interest questionnaires, pretest, and posttest results. The technique of analyzed on students learning interest using the Mann Whitney test because the data are abnormal distributed and learning outcomes using Independent T-Test. Based on the statistical tests, the result showed a good effect of using Quantum Teaching, and Learning (QTL) models influence the interest and learning outcomes of chemistry with experimental class getting learning outcomes was above 80.